Hubungan Dukungan Keluarga dengan Self-Efficacy Menyusui pada Ibu Usia Muda - Nurhaedah, Nurhaedah; Sukarta , Asmah; Roni, Roni (Jurnal MID-Z (MIDWIFERI ZIGOT), 2025)
Globally, less than half of babies under 6 months of age are exclusively breastfed. Breastfeeding Self-Efficacy is a mother's self-confidence in breastfeeding which can be an indicator of the mother's decision, the efforts to be made, the mother's mindset in breastfeeding and how to respond to problems or difficulties during breastfeeding. This type of quantitative research with an analytical research design using a Cross-Sectional approach. The population in this study were all mothers who had breastfed for the past 3 months totaling 81 people, with a sample size of 45 respondents. The results of the study showed that most respondents with high family support had high breastfeeding self-efficacy, namely 19 (42.2%) respondents, while respondents with low family support mostly had low self-efficacy, namely 10 (22.2%) respondents. The results of the chi square statistical test showed that there was a significant relationship between family support and breastfeeding Self-efficacy with a value of ρ = 0.001. The conclusion is that there is a significant relationship between family support and breastfeeding Self-efficacy of Young Mothers, where the higher the family support, the higher the breastfeeding self-efficacy in young mothers